The Use of English in Redefining African Identity by the postcolonial writer case study: half of a yellow sun by chimamandangozi adichie (2008) - Benchaa, Sabrina; Megoussi, Imane; Kourdouli,Abdelkader (Faculty of Letters and Foreign Languages Department of English, 2017)
The use of English by African writers has caused major debate in the literary community as far as the authenticity of the work is concerned. African writings have been questioned because they are written in the language of the coloniser and not in an African language. The first part of the dissertation is based on the theoretical background which discusses the significant use of the colonial language to represent African identity. It also focuses on the postcolonial writer who has been shaped under the influence of two different cultures. The second chapter investigates the issue of identity and its representation in Half of a Yellow Sun by the Nigerian author Chimamanda Ngozi Adichie. In the third chapter, the light is shed on the manifestation of African identity in Half of a Yellow Sun. This dissertation argues that the English language has been used as a linguistic tool which has resulted in a lingual hybridisation